The Influence of Blue Butterfly Pea Flower (Clitoria Ternatea) Gel Extract on Interleukin-10 (IL-10) and Glutathione Peroxidase (GPx) Levels - Siti Asichah; Titiek Sumarawati; Setyo Trisnadi (Window of Health : Jurnal Kesehatan, 2024)
Long-term exposure to Ultraviolet B (UV-B) radiation causes increased skin darkening owing to a reaction to oxidative stress leading to elevated levels of nitric oxide (NO) and reactive oxygen species (ROS). Excessive ROS induces signal transduction and stimulates the transcription factor NF-kβ, an inflammatory mediator. Butterfly flower extract has high antioxidant levels, inhibiting ROS production and reducing inflammatory conditions, hindering MMP, preventing fibroblast cell apoptosis, and inhibiting collagen degradation. However, the role of butterfly pea flowers on IL-10 and GPx gene levels in melasma skin due to UV-B exposure is unclear. This research aims to assess the effectiveness of applying Blue Butterfly Pea Flower Extract Gel on the level of the IL-10 and GPx genes in Wistar rat strains exposed to UV-B. The UV-B-experimental research with the post-test control group. Groups K2, K3, and K4 were each exposed to UV-B at 302 nm with a MED of 160 mJ/cm2, while group K1 was the healthy group. K3 was given 5% butterfly pea flower gel, K4 was given 10% gel daily for 14 days, and K2 received base gel. On the 21st day, ELISA examined the tissue for IL-10 and GPx levels. The IL-10 gene level in the treatment group increased with higher dosages (K3=83.27±3.11, K4=90.66±4.00) compared to controls (K2=33.26±2.98, K1=104.7±3.26). The relative level of the GPx gene in the treatment group increased along with increasing dose (K3=44.90±1.44, K4=54.09±1.00) compared to the control group (K2=29.54±0.85, K1=62.43±0.85). Administration of butterfly pea flower gel can increase the level of the IL-10 gene and the level of the GPx gene in the skin tissue of mouse models of UV-B light-induced hyperpigmentation.